Sarampo no Estado de São Paulo Campanha de Vacinação de Seguimento — 21 de agosto de 2004 - Ciccone, Flávia Helena; R. M. P. Carvalhanas, Telma; S. S. Aranda, Clélia Maria; Keico Sato, Helena (BEPA. Boletim Epidemiológico Paulista, 2004)